2022
DOI: 10.1177/10225536221118521
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic coated nails: Rationale, development, indications and outcomes

Abstract: The concept of antibiotic-coated implants, mainly coated intramedullary nails, has become increasingly used for the treatment of fracture related infections. After a long period of hand-made implants, commercially fabricated implants combine several benefits. Antibiotic-coated nails constitute a solid treatment option for unstable diaphyseal infections with fractures or non-unions. They release high concentrations of antibiotics locally, while retaining reduction and providing axial stability. This review aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The most common complications are similar to those that come with uncoated IMNs including persistent infection and non-union. Additionally, while the following cases are rare, it is essential to be vigilant regarding challenging removal in custom-made implants and potential allergic reactions to the antibiotic agents [32].…”
Section: Discussionmentioning
confidence: 99%
“…The most common complications are similar to those that come with uncoated IMNs including persistent infection and non-union. Additionally, while the following cases are rare, it is essential to be vigilant regarding challenging removal in custom-made implants and potential allergic reactions to the antibiotic agents [32].…”
Section: Discussionmentioning
confidence: 99%
“…Franz et al demonstrated that the use of gentamicin-coated nails in patients with Gustilo-Anderson (GA) type III open tibial fracture led to a lower infection rate and was cost-saving [51]. In their review, Kalbas et al support the use of antibiotic-coated nails [52], in line with De Meo et al, who sustained their use in open fractures and nonunion in high-infectious-risk settings [53]. To modify the kinetic properties, antibiotic-loaded hydrogel coatings such as Defensive Antibacterial Coatings (DACs) have been employed in trauma and prosthetic settings [9,10,45,53].…”
Section: Antibiotic Coatingsmentioning
confidence: 99%
“…2 Three excellent treatment-focused review articles address the relevance of surgical care to the prevention and treatment of fracture related infections, 3 the currently available highest level of evidence to guide our practice 4 and specific aspects on the utilisation of antibiotic coated nails. 5…”
mentioning
confidence: 99%